Effects of co-culture with multipotent endometrial stromal cells during in vitro production of bovine embryos - Camargo, G. C. [UNESP]; Janini, L. C. Z. [UNESP]; Cintra, L. N. [UNESP]; Maciel, A. P. [UNESP]; Sudano, M. J.; Lobo, A. C. M. [UNESP]; Landim-Alvarenga, F. C. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2025)
In vitro embryo production (IVP) protocols generally use supplementation with fetal bovine serum (FBS) in its culture media. Although it contains essential nutrients and growth factors for the embryo, exposure to serum can affect embryonic morphology and biochemistry, in addition to being possibly related to increased fetal weight at birth. In this sense, multipotent stromal cells (MSCs), given the wide range of secreted factors, could help improve IVP protocols. This study verified whether cell proliferation factors secreted by multipotent stromal cells obtained from endometrial tissue (eMSCs) stimulate the development and production of better quality embryos. For that purpose, bovine embryos produced in vitro were co-cultured with eMSCs and evaluated for cleavage index and blastocyst formation, as well as total cell count, trophoblast cell count and apoptotic cell count. It is concluded that the production of bovine embryos associated with co-culture with eMSCs presented similar results to the use of traditional media, showing an improvement regarding the total number of cells, in which the embryos cultivated in the presence of eMSCs and absence of FBS presented a higher number of total cells than those cultured in the absence of eMSCs and FBS.
Keywords: embryos; bovines; IVP; co-culture; stem cells